Miriti (Mauritia flexuosa L. f.): a pérola do Baixo Tocantins - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2023)
The book "Miriti: the pearl of the Baixo Tocantins" features descriptions, stories, and quotes from artisans, adorned with visual content that beautifully portrays the way of life, work, landscape, and the distinctive nature of the miriti, which flourishes along the riverbanks of the municipality of Abaetetuba, affectionately known as "The Pearl of the Lower Tocantins." Revisiting one of the municipality's symbols, the anthem composed by Máximo Ribera, which portrays the following excerpt: "Maratauíra, a great and beautiful river, a strong arm of the immense Tocantins, has on its banks a majestic corner of work mixed with feasting." The book's theme is harmoniously intoned, a hymn in praise of the festive work with miriti by the artisans of Abaetetuba, who sculpt, paint, mold, weave, build, and cook their stories, their ancestry, and their love for their culture.
Miriti (Mauritia flexuosa L. f.): the pearl of the Baixo Tocantins
Keywords: Miriti; Etnobotânica; Botânica econômica; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA